Collective Action in Canal Irrigation Systems Management: The Case of Doho Rice Scheme in Uganda, 2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
The study that the Collective Action in Canal Irrigation Systems Management: The Case of Doho Rice Scheme in Uganda, 2001 survey data was collected for examines the extent and determinants of farmer participation in the collective maintenance of Doho Rice Scheme (DRS) and compliance in paying mandated irrigation fees. Existing regulations and incentives for participation in collective action are also examined.The objective of this study is to determine the extent of farmers’ participation in the collective action of maintaining the DRS canals after the transfer of the responsibility from the government, and to identify factors influencing farmers participation and compliance with a user-fee payment bylaw. The study was conducted at the DRS in Tororo District, Uganda through a survey of 411 households that produced rice in the first or second crop seasons in 2001.